Reflexiones sobre la vejez y el envejecimiento en la narrativa testimonial de Teresa Pàmies - Natale, Daniela (Dialogoi. Rivista di studi comparatistici, 2020)
This paper inquires into Teresa Pàmies’s last writings on aging: their motivations, goals and thoughts, and how the studies on this subject have political implications for women and feminism. The writer started publishing her novels and essays, at the end of her exile, when she was fifty-two years old, when her active militancy had come to en end. The old age had always been one of the themes of her works where she dared to contradict the hegemonic representation of femininity, based on youth and beauty, supporting the women’s associations that fight against social exclusion and the marginalization of elderly women.